2010
DOI: 10.1117/12.866683
|View full text |Cite
|
Sign up to set email alerts
|

Effect on surface roughness of zerodur material in atmospheric pressure plasma jet processing

Abstract: Zerodur material is considered as the ideal material in the high performance optic systems because of its excellent thermal stability characteristics. This paper deals with the impacting factors on the zerodur material surface roughness during atmospheric pressure plasma jet(APPJ) processing. At first, based on multiphase and multi-component in zerodur material, the effect on the zerodur surface chemical components and surface roughness is studied when the element contained Si is etched during the chemical mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Yao et al and Jin et al presented plasma machining of Zerodur using a RF-excited plasma jet at atmospheric pressure. It was shown that the surface roughness was strongly dependent on the process parameters and in particular on the mixing ratio of the working gas, SF 6 and O 2 [6,7]. However, such plasma figuring methods can provoke surface roughening due to inhomogeneous etching, an effect which was also observed in the case of reactive ion etching (RIE) of pyrex glass [8].…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al and Jin et al presented plasma machining of Zerodur using a RF-excited plasma jet at atmospheric pressure. It was shown that the surface roughness was strongly dependent on the process parameters and in particular on the mixing ratio of the working gas, SF 6 and O 2 [6,7]. However, such plasma figuring methods can provoke surface roughening due to inhomogeneous etching, an effect which was also observed in the case of reactive ion etching (RIE) of pyrex glass [8].…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al 58 evaluated the influence of various process parameters on APPJ processed zerodur substrates. Also, the modification of the surface chemistry is studied in detail.…”
Section: Plasma Polishing Methods Applied To Various Optical Componentsmentioning
confidence: 99%
“…The effect of dwelling time (min) and O 2 /SF 6 ratio on surface roughness (Figure 5(a) and (b), respectively), up to 30% improvement in the surface finish is obtained. 58 The relation between the substrate's surface roughness and the process parameters is reported based on the experimental results.…”
Section: Plasma Polishing Methods Applied To Various Optical Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low-pressure (10 −2 -0.5 mbar) plasma method can reduce the subsurface damage on freeform and complex surfaces. The different working gases are successfully used in atmospheric pressure plasma to reduce the subsurface damages while achieving an ultralow surface finish [12][13][14]. APPP processes are limited to small apertures and do not apply to freeform surfaces.…”
Section: Introductionmentioning
confidence: 99%